2017
DOI: 10.5603/kp.a2017.0122
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-related peculiarities of patients with delirium in the cardiac intensive care unit

Abstract: A b s t r a c t Background:The overall evidence base regarding delirium has been growing steadily over the past few decades. There has been considerable analysis of delirium concerning, for example, mechanically ventilated patients, patients in the general intensive care unit (ICU) setting, and patients with exclusively postoperative delirium. Nevertheless, there are few studies regarding delirium in a cardiovascular ICU (ICCU) setting and especially scarce literature about the particular features of delirium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…Regarding the association between gender and cognitive function, there is evidence for a female advantage in episodic memory for verbal information and a male advantage in visuospatial memory TA B L E 2 Factors associated with POD in patients over 70 years in the two groups (Beinhoff, Tumani, Brettschneider, Bittner, & Riepe, 2008). Further analysis revealed that men with a more prevalence of sepsis, coronary artery disease, hyponatremia, and hypokalemia, and women with hypertension, conduction disorders, myocardial infarction, and dementia presented a higher incidence of delirium (Serpytis et al, 2017). However, the frequency of delirium after surgery was similar between women and men in many reports (Hogue, Sundt, Barzilai, Schecthman, & Davila-Roman, 2001).…”
Section: Days After Surgerymentioning
confidence: 99%
“…Regarding the association between gender and cognitive function, there is evidence for a female advantage in episodic memory for verbal information and a male advantage in visuospatial memory TA B L E 2 Factors associated with POD in patients over 70 years in the two groups (Beinhoff, Tumani, Brettschneider, Bittner, & Riepe, 2008). Further analysis revealed that men with a more prevalence of sepsis, coronary artery disease, hyponatremia, and hypokalemia, and women with hypertension, conduction disorders, myocardial infarction, and dementia presented a higher incidence of delirium (Serpytis et al, 2017). However, the frequency of delirium after surgery was similar between women and men in many reports (Hogue, Sundt, Barzilai, Schecthman, & Davila-Roman, 2001).…”
Section: Days After Surgerymentioning
confidence: 99%
“…Los pacientes que son sometidos a cirugía cardiaca atraviesan una serie de alteraciones que afectan sus funciones fisiológicas y las motoras y/o cognitivas, lo que conlleva a una disminución en la capacidad para desarrollar las actividades de la vida diaria, generando así, un déficit de autocuidado (21,22). Adicionalmente, la escala utilizada en este estudio es útil para medir el estado funcional de las personas cuando son dadas de alta de un servicio de cuidado intensivo (23).…”
Section: Discussionunclassified
“…Del mismo modo, se evidenció que durante la medición posterior a la cirugía, los pacientes presentaban mayor dependencia para la ejecución de sus actividades de la vida diaria explicado por las limitaciones para la movilización tales como: accesorios de uso terapéutico (sondas, drenes, catéteres, vía aérea artificial), inestabilidad hemodinámica y respiratoria (24). También se debe precisar, que el cuidado intensivo postoperatorio de la cirugía cardíaca, tiene como objetivo la recuperación de la homeostasis que se ve afectada por los cambios fisiopatológicos generados por el uso de la circulación extracorpórea, los fenómenos de isquemia-reperfusión en el corazón, la hipotermia, trastornos en el sistema de coagulación y los efectos adversos de las transfusiones y el sangrado (23,25); por tanto, el reposo en cama puede conllevar al desacondicionamiento físico (26).…”
Section: Discussionunclassified
“…There is little research on whether gender affects the occurrence of the POD. According to a study 32 , delirium was more often affected men amongst patients under 65 years old and more frequently affected women in the age group of over 85 movement can also help treat patients, and it is also necessary to create an environment to help patients recover by using the items needed for each patient.…”
Section: Risk Factors Of the Podmentioning
confidence: 99%